Abnormal Cystic Tumor in a Patient with Hereditary Leiomyomatosis and Renal Cell Cancer Syndrome: Evidence of a Precursor Lesion? - Benjamin T. Ristau; Sonal N. Kamat; Tatum V. Tarin (Case Reports in Urology)
The hereditary leiomyomatosis and renal cell cancer (HLRCC) association is a rare syndrome caused by mutation of the Kreb’s cycle enzyme, fumarate hydratase (FH). It is characterized by unusually aggressive type 2 papillary renal cell histology. FH is responsible for catalyzing the conversion of fumarate to malate. Its absence leads to a state of “pseudohypoxia,” inducing hypoxia inducible factor 1α (HIF-1α) and leading to increased growth factor transcription (e.g., vascular endothelial growth factor, VEGF; glucose transporter 1, GLUT1). Ultimately, this results in tumorigenesis. We present a patient who was diagnosed with HLRCC and underwent bilateral nephrectomies. One of the nephrectomy specimens was notable for benign cystic lesions that stained positive immunohistochemically for succinated proteins, a finding only noted in FH-deficient cells. Thus, we posit a potential precursor lesion to type 2 papillary renal cell carcinoma in the HLRCC syndrome.